If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 112 = 180 Reorder the terms: 112 + Y = 180 Solving 112 + Y = 180 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-112' to each side of the equation. 112 + -112 + Y = 180 + -112 Combine like terms: 112 + -112 = 0 0 + Y = 180 + -112 Y = 180 + -112 Combine like terms: 180 + -112 = 68 Y = 68 Simplifying Y = 68
| 10x-32=0 | | 10x+6=6x+34 | | 0.5(x+2)+5=9 | | 2w+3=3 | | 3+10x=93+x | | 6n+21=4n+57 | | 10x+4-3x=-45 | | 7.32=0.05x-0.18 | | (4x-10)+(2x+15)+x=180 | | 3x+28=12x-71 | | 11x-32=6x+3 | | 6x+5=180 | | 2(0)+5y=-10 | | 2x+5(0)=-10 | | p^2-11p-5=0 | | -2(-7-7x)=-98 | | -(4x-8)= | | -6(x+3)-3x=-81 | | -2r-2(8-6r)=-86 | | 3y+3=4x | | -7(4x+6)=-210 | | 7(0)-5y=35 | | -102=4(7r+4)-6 | | 7x-5(0)=35 | | -5(5+7n)=255 | | .1429x+2z=5+x-z | | 136-2x=34x+16 | | x^3+8x=0 | | y=.20(5)-2 | | 140=7(-2a+4) | | 14-10x=72-24x | | -7(5+3n)=-203 |